The Psychological Foundations of Management in Family Firms: Emotions, Memories, and Experiences. (June 2021) - Humphrey, Ronald H.; Massis, Alfredo De; Picone, Pasquale Massimo; Tang, Yi; Piccolo, Ronald F.
Exploring the psychological foundations of management in family firms is necessary to understand why they formulate and implement strategies differently from nonfamily firms, and why and how family firm behavior varies across different family firms. Picone et al. (2021. The psychological foundations of management in family firms: Values, biases, and heuristics. Family Business Review, 34 (1), 12-32) have proposed a conceptual framework for the psychological foundations of management in family business, examining how the values, biases, and heuristics of family firm members affect strategic decision-making and family firm outcomes. Drawing on this framework, we examine emotions, memories, and experiences in family firms, disentangling "what we know" from "what we should know", and offering some relevant questions to advance the field.